Sharia Fintech to Create Crowdfunding Donations for Islamic Boarding Schools - Robiatul Auliyah; Basuki Basuki (InFestasi, 2022)
The objective of this study was to export the application of sharia fintech to create crowdfunding donations (CFD) for Islamic boarding schools in productive business activities in terms of S-O-R theory. The Discourse Analysis (DA) approach was used to see the discourse on the websites of Kitabisa.com, Republika, Youtube, and journals and strengthened by 2 informants, including Ahmad (pseudonym) who was an expert in sharia, and Mrs. Ayu as a business player who donated money through the website. The code determination used NVIVO 12 and XMind software in linking the code to obtain meaning in each code. The results of this study found that a stimulus that uses technology to raise donations is supported by a quality web so that transactions are more comfortable. The organism code consists of simple, responsible, and viral, there are four codes, namely, the message is unique and interesting as a category of simple. Responsible, there is a code of transparency and virality expressed in the stories of donors who are told in response to giving opportunities for goodness, hearts becoming peaceful, fields of reward, and being able to build the economy. Research on CFD in Indonesia is rarely conducted in Islamic boarding schools. Previous research mainly discussed CFD for social interests, while this study discussed donations for productive business interests for Islamic boarding schools to support government programs to have excellent products and generate santriprenuers.